At the Edge of the Internet: Teaching Coding and Sustainability to Himalayan Girls - Frances Garrett; Matt Price; Laila Strazds; Dawn Walker (The Canadian Network for Innovation in Education (CNIE), 2020)
This report introduces a two-week workshop on web coding and environmental sustainability at a school for girls in northeastern India. Our discussion of this teaching project reviews issues that shaped the project's development, outlines resources required for implementation, and summarizes the workshop's curriculum. Highspeed internet will soon arrive in the region of this recently-recognized UNESCO World Heritage Site. We believe that the training of girls in particular could help redistribute power and resources in regions where women are often poorer, less educated, and excluded from decision-making in institutional and public contexts. Relatively few code teaching projects have grappled with the difficulty of working in offline environments at the "edge of the internet," and yet moving skills and knowledge into these regions before the internet arrives in full force might help mitigate some of the web's worst impacts on equity and justice.